Incorporating Opioids into Micro - to Nano - Structurally Optimized Silica Xerogel Controlled Release Delivery Systems Prevents Abuse - Toworfe, George K. (European Scientific Journal, ESJ, 2019)
Analgesics is a multibillion dollar worldwide industry. Oxycodone, an opioid, is currently administered using controlled release tablets; although this has resulted in considerable control over pain management, the controlledrelease tablets have been abused by drug users. Measures to curb illicit use of the drug have not been successful, to date. This study proposes that by incorporating the medicine into a micro- to nano-structurally optimized delivery material, release concentrations that cannot exceed therapeutic target levels will be achieved and therefore, curbing its misuse, even when the carrier material is crushed. Using Dextromethorphan (Dextro) as a model drug, silica xerogels (sol-gels) were synthesized by mixing tetramethoxysilane, Deionized water and HCl, in addition to Dextro-methanol solution. Different drug loads and water-to-alkoxide ratios were observed to alter the micro- and nanostructurural properties. Different particle sizes were produced by crushing the xerogel discs, after which they were sieved and immersed in 5mg/ml PBS solution. Concentration of released Dextro was measured spectrophotometrically at 280 nm. The effect of particle size on in vitro release of Dextro from xerogels, as a function of immersion time, demonstrated that both micro- to nano-sized particles exhibited timedependent release of Dextro. Although the release from nano-sized particles was noticeably faster than from the micro-sized ones, they did not show any burst release. Data obtained demonstrate that synthesizing a delivery system capable of achieving the controlled-release of therapeutically relevant doses and misuse resistance are attainable.